Greenness moderates the relationship between self-rated social standing and depression among older adults in the Canadian longitudinal study on aging - Irvin, Alexa; Dutton, Daniel J.; Kirkland, Susan; Rainham, Daniel G.; Asada, Yukiko (Frontiers in Environmental Health, 2024)
Greenness is considered to be a health-promoting feature of both natural and built environments and has the potential to influence mental health outcomes. However, most studies to date have neglected to address whether greenness differentially affects mental health outcomes for individuals across the socioeconomic spectrum. Our study explored if greenness is a moderating factor in the relationship between socioeconomic status (SES) and mental health using data from the Canadian Longitudinal Study on Aging (CLSA). We used self-rated social standing as a measure of SES and depression score measured using the Centre for Epidemiologic Studies 10-Item Depression Scale (CESD-10) as a measure of mental health. Greenness was measured using the annual maximum Normalized Difference Vegetation Index (NDVI) within a 1000 m buffer area of participants' residential postal code locations. There was a statistically significant moderating effect of greenness for the relationship between self-rated social standing and depression score. As greenness increased, individuals with lower self-rated social standing had the greatest decreases in depression score. This suggests that targeting greening interventions at individuals and communities with low SES may reduce depressive symptoms overall, as well as decrease socioeconomic inequalities in depression.